The empirical investigation of the difference between socially responsible and vice investing returns - Lönnqvist, Jere (My University, 2022)
Socially responsible investing has increased significantly in recent years due to the increased demand. The ideology of socially responsible investing is to invest in businesses that support sustainable and ethical choices. Alongside it has developed an opposite vice investing strategy. In the vice investing strategy, the investors see that the related assets are undervalued due to their reputation and possible risks. This research examines the difference between the risk-adjusted returns of socially responsible and vice investing strategies in the United States from 2018 to 2021. The performance evaluation is done by the Capital Asset Pricing Model, Fama & French three- & five-factor models, Carhart’s four-factor model, Jensen’s alpha, and the Sharpe ratio. The research results indicate that the socially responsible investing strategy outperforms the vice investing in all models. The results are not statistically significant. Thus, the academic evidence of the findings is weak. However, the research offers a solid ground for future studies.
Keywords: corporate responsibility; social responsibility; ethical investing; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance